PERAN KEPEMIMPINAN ISLAM DALAM MENDORONG ETIKA ORGANISASI STUDI TENTANG PENERAPAN NILAI-NILAI ISLAM DALAM BISNIS MODERN - Amalia, Barizah (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
This study aims to explore how Islamic values can be applied in modern business environments to promote organizational ethics. The methodology used in this research includes a literature review and analysis of relevant literature. The results indicate that the implementation of Islamic leadership values such as honesty, justice, responsibility, and consultation can enhance organizational ethics and company performance. Furthermore, this study evaluates the challenges and opportunities in applying Islamic values in daily business practices. By understanding and integrating Islamic values into business practices, organizations can achieve a balance between profit-making and fulfilling social responsibilities, while also contributing positively to society and the surrounding environment